(untitled) (Olhar de Professor, 2022)
Through the critical analysis of the National Common Curricular Base - BNCC, the aim was to analyze and understand how the corporal practices of the fights are understood, presented, founded and organized by this document, seeking to analyze the main advances and setbacks in relation to this thematic process. The analyzes were organized in three axes. In the first, we present an overview of the Physical Education curricular component according to the BNCC. In the second, we understand the practices of fights in the Physical Education classes. In the third, we establish an analysis about how the BNCC presents the pedagogical organization on the teaching of fights. It is concluded that although the BNCC ensures the fights as one of the thematic of Physical Education, the document contributes to the silencing of these practices by presenting few proposals for an approach that in fact show their social and historical importance.